COMPARISON OF BORED PILE AXIAL BEARING CAPACITY BASED ON VESIC’S METHOD (1970), STANDARD PENETRATION TEST (SPT), AND LOADING TEST IN THE PROJECT OF ELEVATED TOLL ROAD JAKARTA – CIKAMPEK STA.9+500 – STA.47+000 - Sofyan Suri; Martinus Agus Sugianto (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2018)
As a foundation under the structure can be generally divided into two types, namely the foundation deep and shallow foundation. Selection of the type of foundation depends on the type of structure including the construction load on whether light or heavy loads and also depending on the soil type. For the construction of a light load and soil conditions quite well, usually worn shallow foundation, but the construction of a heavy load is usually the type of deep foundation is the right choice.In general, the more complex the deep foundation of a shallow foundation. To this writer tried to concentrate on planning the foundation of this thesis in which bored pile (Bored Pile Foundations). Bored Pile foundation is a foundation built by drilling the ground first, then filled with steel reinforcement and cast. Bored pile used when soil solid base which has a carrying capacity of it lies very deep, which is approximately 15 m as well as the state of the soil around the many stands a large building and rise to the feared could lead to cracks in the existing building effect vibrations caused by staking activity when administered pile foundation. Carrying capacity of bored pile end bearing capacity is obtained than that obtained from pressure and friction pile tip bearing capacity obtained from carrying friction or adhesion force between the bored pile and the surrounding soil.Keyword:Bored Pile, Axial Bearing Capacity, SPT, Loading Test